(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
The lift-the-flap book learning media is classified as a new learning medium in Islamic Religious Education (PAI) and Character Education (BP), thus requiring an effectiveness test. This study aims to analyze the effectiveness of the lift-the-flap book learning media on the learning outcomes of first-grade elementary school students in PAI and BP subjects. This study employs a quantitative approach with an experimental method. The research design used is a quasi-experimental design with a nonequivalent control group design. The study population consists of 77 individuals, with a sample size of 51 individuals selected through purposive sampling. Data collection was conducted using pretests and posttests, while data analysis was carried out using descriptive and inferential statistical methods with the assistance of IBM SPSS Statistics 26 software. The study results indicate that t_count > t_table, where t_count = 10.006 and t_table = 2.06390, with a significance probability (P-value) of 0.000, making sig. (2-tailed) < 0.05. Therefore, H₀ is rejected, and Hₐ is accepted, indicating that the use of lift-the-flap book learning media is effective in improving learning outcomes. Furthermore, the N-Gain Score test results show that the experimental group achieved a score of 57.23%, classifying it as moderately effective, while the control group obtained a score of 47.79%, which is classified as less effective. Based on these findings, it can be concluded that the use of lift-the-flap book learning media is moderately effective in improving PAI and BP learning outcomes for first-grade elementary school students.